The Power of Celebrity Endorsements: Examining the BarenBliss Brand Image among TikTok Users - Aprianto, Ronal; Surajiyo, Surajiyo; Suwarno, Suwarno; Santia, Yeyen (Pandawan Sejahtera Indonesia, 2024)
The purpose of this study is to ascertain how the Barenbliss brand is impacted by the visibility, credibility, attraction, and power of celebrity endorsers among Lubuklinggau Private University TikTok users. With a sample of 150 students who used the TikTok app, the study's population consisted of all enrolled private university students, or roughly 2057 students. The Smart PLS 3 analysis tool is used in this study's quantitative data processing methodology. The study's findings indicate that, first, the visibility variable of celebrity endorsers has no effect on the Barenbliss brand image; second, credibility positively affects brand image; and third, attraction has no effect on brand image. Brand Image, fourth, demonstrates that strength has a significant impact on brand image; fifth, it has positive significance because the t-statistic value of Visibility (X1) and Credibility (X2) on Brand Image (Y) is t-count greater than t-table; sixth, it has positive significance because the t-statistic value of Attraction (X3) and Power (X4) on Brand Image (Y) is greater; seventh, it is negative because the t-statistic value is smaller than the t-table; ninth, it is positive because the t-statistic value is smaller than the t-table; and, for testing all variables X against variable Y, significant positive results are obtained because the t-value-statistics is greater than the t-table.